2006
DOI: 10.1111/j.1471-4159.2006.03842.x
|View full text |Cite
|
Sign up to set email alerts
|

Two members of the TRPP family of ion channels, Pkd1l3 and Pkd2l1, are co‐expressed in a subset of taste receptor cells

Abstract: Taste receptors cells are responsible for detecting a wide variety of chemical stimuli. Several molecules including both G protein coupled receptors and ion channels have been shown to be involved in the detection and transduction of tastants. We report on the expression of two members of the transient receptor potential (TRP) family of ion channels, PKD1L3 and PKD2L1, in taste receptor cells. Both of these channels belong to the larger polycystic kidney disease (PKD or TRPP) subfamily of TRP channels, members… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
121
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(126 citation statements)
references
References 71 publications
2
121
2
1
Order By: Relevance
“…Salty and sour stimuli are likely transduced by different cells than are bitter, sweet, and umami tastants because they are not believed to be transduced through cells expressing G-proteincoupled taste receptors and PLC␤2 (Huang et al, 2006;Ishimaru et al, 2006;Lopez-Jimenez et al, 2006). It is not confidently known which class of taste cells (i.e., receptor, presynaptic) is involved in salty and sour taste transduction.…”
Section: Presynaptic Cells Respond To Sour and Salty Stimulimentioning
confidence: 99%
“…Salty and sour stimuli are likely transduced by different cells than are bitter, sweet, and umami tastants because they are not believed to be transduced through cells expressing G-proteincoupled taste receptors and PLC␤2 (Huang et al, 2006;Ishimaru et al, 2006;Lopez-Jimenez et al, 2006). It is not confidently known which class of taste cells (i.e., receptor, presynaptic) is involved in salty and sour taste transduction.…”
Section: Presynaptic Cells Respond To Sour and Salty Stimulimentioning
confidence: 99%
“…Lopez Jimenez et al [25] first reported the expression of these channels in a subset of mouse taste cells. Later, Ishimaru et al [26] confirmed and extended those findings by expressing PKD1L3 and PKD2L1 in HEK293 cells and showing that the transfected cells generated an inward current upon acid stimulation.…”
Section: Sour Transduction Mechanismsmentioning
confidence: 99%
“…Both strong acids, such as hydrochloric acid, and weak acids, such as acetic or citric acid, produce a sour sensation in humans and evoke sensory responses in nerve recordings in a variety of model organisms, including rat, mouse, and hamster (4)(5)(6)(7). A number of molecules have been proposed to transduce sour taste, most recently the ion channel PKD2L1/PKD1L3 (8)(9)(10)(11)(12), but their role in taste transduction remains unclear as subsequent studies using knockout mouse strains have failed to identify significant effects on sour taste (13)(14)(15). Nonetheless, the Pkd2l1 gene serves as a useful marker for sour taste cells (also designated type III cells), which account for ∼10% of the ∼50-100 taste cells found in each taste bud (1,9,11,16,17).…”
mentioning
confidence: 99%
“…A number of molecules have been proposed to transduce sour taste, most recently the ion channel PKD2L1/PKD1L3 (8)(9)(10)(11)(12), but their role in taste transduction remains unclear as subsequent studies using knockout mouse strains have failed to identify significant effects on sour taste (13)(14)(15). Nonetheless, the Pkd2l1 gene serves as a useful marker for sour taste cells (also designated type III cells), which account for ∼10% of the ∼50-100 taste cells found in each taste bud (1,9,11,16,17). Previously, using a Pkd2l1-YFP mouse, we showed that sour cells express a unique Zn 2+ -sensitive proton conductance, of unknown identity, that is likely to mediate the initial event in taste transduction (16).…”
mentioning
confidence: 99%